Salmonella occurrence and myoglobin (mb) in frozen smoked tuna - Korah, Herny; Ijong, Frans G.; Suwetja, I Ketut (AQUATIC SCIENCE & MANAGEMENT, 2015)
Title (Bahasa Indonesia): Keberadaan salmonella dan tingkat kesegaran frozen smoked tuna This study aimed to quantify Salmonella, Total and Total Plate Count (TPC) in fresh tuna loin, frozen tuna loin, and frozen tuna loin filled with CO gas, to analyze the level of freshness of the fish through the test Mb, pH and appearance in fresh tuna loin, frozen tuna loin and frozen tuna loin filled with CO gas, and to describe the presence of Salmonella and the provision of value Mb with CO gas. Object of study in this research is the bacterium Salmonella and Myoglobin (Mb) in frozen smoked tuna, through the fish freshness analysis (Mb value test, pH, and organoleptic), TPC analysis, total Salmonella in fresh tuna (as a positive control), frozen tuna loin and frozen tuna loin frozen filled with CO gas. Results showed total Salmonella after incubation at 37 ° C for 24 and 48 hours fresh tuna loin, frozen tuna loin, and frozen tuna loin frozen filled with CO gas were 4.80 x 102 CFU/g and 5.43 x 102 CFU/g; 0.57 x 10 CFU/g and 1.55 x 102 CFU/g; 3.90 x 102 CFU/g; and 8.63 x 102 CFU/g, respectively. Total Salmonella tended to decline in frozen tuna, but increase in frozen tuna CO at 48 hours incubation. Mb value was 1.02 for fresh tuna loin, 0.86 for frozen tuna and 0,92 for frozen tuna filled with CO gas, respectively. The pH value was 5.23 in fresh tuna loin, 6.10 in frozen tuna loin, and 6.24 in frozen tuna loin filled with CO gas. Organoleptic value showed that fresh tuna loin was attractive to very attractive, frozen tuna loin was attractive and frozen tuna loin with CO gas was very attractive. TPC incubated at 37 ° C for 24 hours for fresh tuna loin was 11.75 x 103 CFU/g, for frozen tuna loin was 1.66 x 103 CFU/g, and frozen tuna loin with CO gas was 1.54x103 CFU/g. TPC incubated at 37 ° C for 48 hours for fresh tuna loin was 12,13x103 CFU/g, frozen tuna loin was 1.73 x 103 CFU/g, and frozen tuna loin with CO gas was CO 1.99 x 103 CFU/g. Penelitian ini bertujuan untuk menganalisis tingkat kesegaran ikan, menghitung Total Plate Count (TPC) dan total Salmonella pada tuna loin segar, tuna loin beku, dan tuna loin beku yang diberi gas CO, serta mendeskripsikan keberadaan Salmonella dan tingkat kesegaran frozen smoked tuna. Objek kajian dalam penelitian ini adalah isolat Salmonella dan Mioglobin (Mb) pada frozen smoked tuna, dengan menganalisis kesegaran ikan (uji nilai Mb, pH dan organoleptik), analisis TPC, total Salmonella pada tuna segar (sebagai control positif), tuna beku dan tuna beku yang diberi gas CO. Hasil penelitian menunjukkan bahwa Total Salmonella yang diinkubasi pada suhu 37OC selama 24 dan 48 jam untuk tuna loin segar, beku dan beku yang diberi CO berturut-turut : 4,80 x 102 CFU/g dan 5,43 x 102 CFU/g; 0,57 x 10 CFU/g dan 1,55 x 102 CFU/g; 3,90 x 102CFU/g; dan 8,63 x 102 CFU/g. Total Salmonella cenderung menurun pada tuna beku, tetapi naik pada tuna beku CO dengan lama inkubasi 48 jam. Nilai Mb masing-masing adalah: 1,02 untuk tuna segar, 0,86 untuk loin tuna beku dan 0,92 untuk loin tuna beku yang diberi gas CO. Nilai pH 5,23 untuk loin tuna segar, 6,10 untuk loin tuna beku dan sebesar 6,24 untuk loin tuna beku yang diberi gas CO. Nilai organoleptic 7,55 untuk loin tuna segar ( diantara menarik dan sangat menarik), 7,35 loin tuna beku (menarik) dan 7,75 loin tuna beku yang diberi gas CO (sangat menarik). TPC yang diinkubasi pada suhu 37OC selama 24 jam adalah 11,75 x 103 CFU/g untuk loin tuna segar, 1,66 x 103 CFU/g untuk loin tuna beku dan 1,54 x 103 CFU/g untuk loin tuna beku yang diberi gas CO sebesar. TPC yang diinkubasi pada suhu 37OC selama 48 jam 12,13 x 103 CFU/g untuk loin tuna segar, 1,73 x 103 CFU/g untuk loin tuna beku dan 1,99 x 103 CFU/g untuk loin tuna beku yang diberi gas CO.